The evaluation of depression, anxiety, and stress among undergraduate dental students in graduation year in Mainland China: a cross-sectional study - Ying Fang; Mingya Yang; Wenyan Huang; Yijing Zhang; Xuguang Gao; Yijing Chen; Si Meng; Sujuan Zeng (BMC Medical Education)
Abstract Background Mental health issue in dental students has emerged as a worldwide concern. This study aims evaluate the mental health status among undergraduate dental students in their final year in mainland China, and to investigate the association factors behind it, aiming for better understanding of current situation of dental education and provide some perspectives. Methods An analytical cross-sectional study was conducted using an Internet-based survey platform to collect data from undergraduate dental students in their final year in mainland China. The DASS-21 instrument was used to evaluate mental health outcomes, while a supplementary questionnaire was designed to gather information on their university experience and satisfaction across various aspects. The relationship between socio-educational characteristics and mental health was then analyzed. Results Varying levels of depression, anxiety, and stress were found among investigated participants. The mental problem was found related to gender (p < 0.01), school levels (p < 0.001), and regions (p = 0.001). Regression analysis identified several factors correlating with DASS-21 scores, with concerns about physical appearance being particularly prominent among students. Conclusion Undergraduate dental students in final year in mainland China experience significant mental health challenges, including depression, anxiety, and stress. Factors including gender, school levels, and regions all showed significant difference in stress, depression, and anxiety. Besides, various academic and social reasons would contribute to that. Social support should pay more attention to mental health in dental students.